A Network-based framework for strategic conflict resolution - Powell, J. H. (Department of Defence Management and Security Analysis, 2009)
Strategic conflict in this work refers to the spectrum of co-operative and oppositional activities in which organisations engage when their interests meet. The origin of the work is in the management and prediction of corporate strategic conflict, but it will be seen that there are significant similarities between corporate struggle and that of international relations. Following a review of the nature of conflict and the characteristics of strategic decision making, the work examines the effectiveness of three existing general approaches to conflict modelling and management, namely informal and qualitative methods; general systems analysis methods; and game theoretic approaches. Desirable criteria for a strategic conflict management framework are derived and a framework is then proposed which has three components: - Setting thefuture environment The future of the organisation is described by a network of states of nature. Resolving the Conflict Within each of the states which represent the future, the options for participants are identified and the possible outcomes and interim states identified. An analysis of the influence and power of the participants over transitions between states is carried out, which indicates likely development paths in the conflict, from which conclusions can be drawn about both the likely outcomes, and about the actions which should be taken by a company to bring about preferred outcomes. Closing the Loop Feedback of information obtained by analysis and by contact with the real world back into the two structures described above allows examination of the effect of changing perspectives and the differing beliefs of participants. The application of the framework is shown through case studies examining thejustifiability and appropriateness of each of its elements and as a whole. These case studies cover both small and large companies, a variety of business conflict cases, both live and retrospective and draw on the recorded material in international relations for examples of non- . commercial conflict. Future development paths are identified for the concept
Keywords: Peace building; Conflict management; Interpersonal conflict; Conflict (Psychology)